Study of Various Obstacles to Vertical Land Consolidation for Kampung Improvement Program (Case Study: Pilot Project of Vertical Land Consolidation in Cipinang Besar Selatan, East Jakarta, 2022) - Yustiningrum, Nurlina; Adianto, Joko (Smart City, 2024)
The study examines the challenges encountered in the implementation of the Vertical Land Consolidation (VLC) program, which primarily focuses on providing homes through the Kampung Improvement Program in Jakarta Province. VLC, or Vertical Land Consolidation, is an essential approach to improving the security of land ownership and the quality of housing in densely populated, degenerated metropolitan areas that face numerous obstacles. A significant challenge is the requirement for voluntary involvement from a minimum of 60% of people in the area, emphasizing the importance of bottom-up planning. The study was conducted in 2022 at Cipinang Besar Selatan (East Jakarta) using a case study methodology. The results indicate that the implementation of the program faces difficulties as a result of implementing top-down approaches and ongoing issues with tenure security. The study highlights the importance of combining top-down techniques with bottom-up community engagement to enhance the efficiency of VLC initiatives in urban kampungs, specifically in metropolitan locations like Jakarta.